Legal Protection for Indonesian Family-Owned Company Minority Shareholders: Comparative Study with Germany and Australia - Gautama, Abhiyoga Dirdanaraputra; Dewi, Yetty Komalasari (Halu Oleo University, 2022)
This paper examines the legal protections provided for Minority Shareholders in Family–Owned Company in Indonesia, Germany and Australia. It further examines whether the Company Law has provided a sufficient legal protection for Minority Shareholders in Indonesia Family – Owned Company after comparing with the equivalent regulation in Germany and Australia. Based on the juridical- normative research which uses statutory and comparative approach, it resulted that there are similarities and differences of Minority Shareholders protection provided by each country, in which the different protections are: (i) Rights on Equal Treatment; (ii) Rights to Appoint and Revoke Management; (iii) Restraint on Contravention; dan (iv) Rights to Information. This paper concludes that Indonesia has not provide a sufficient legal protection for Minority Shareholders compared to Germany and Australia due to the protections which have not yet been regulated under the Company Law while the protections will help provide a more certainty in protecting Minority Shareholders to obtain its rights in Family-Owned Company. Thus, this paper recommends that the unregulated protections shall be added to Company Law to ensure the rights of Minority Shareholders and to reduce oppressive act by Majority Shareholders in Family-Owned Company.